2022
DOI: 10.21037/atm-22-3858
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of m6A-related signatures associated with the tumor immune microenvironment and predict survival in acute myeloid leukemia

Abstract: Background Most previous studies have focused on the intrinsic carcinogenic pathways of tumors; however, little is known about the potential role of N6-methyladenosine (m6A) methylation in the tumor immune microenvironment (TIME). To better diagnose and treat acute myeloid leukemia (AML), we sought to examine the correlation between m6A regulatory factors and immune infiltration in cases of AML. At the same time, a prognostic model was constructed to predict the survival of AML. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The LASSO algorithm examines multiple independent variables at once and identi es the most impactful ones. With the LASSO algorithm, it is possible to concurrently evaluate numerous independent variables and pinpoint the variables with the greatest in uence.According to the traditional regression methods are considerably less precise.Based on LASSO Cox analysis, prognostic factors for relapsed B-ALL were identi ed, including RBM15B, YTHDC1, YTHDC2, FTO, and HNRNPC among the 20 genes analyzed [11] .The ROC curve was used to evaluate the impact of m6A methylation related genes on the prognostic outcome of relapsed B-ALL.The ndings indicated that genes associated with m6A methylation played a role in the survival of relapsed B-ALL.The risk score of m 6 A methylation-related genes (YTHDC1 and FTO) might be a powerful biomarker for relapsed B-ALL survival. High expression levels of FTO predicted a poor prognosis, whereas YTHDC1 can be regarded as protective genes.…”
Section: Discussionmentioning
confidence: 99%
“…The LASSO algorithm examines multiple independent variables at once and identi es the most impactful ones. With the LASSO algorithm, it is possible to concurrently evaluate numerous independent variables and pinpoint the variables with the greatest in uence.According to the traditional regression methods are considerably less precise.Based on LASSO Cox analysis, prognostic factors for relapsed B-ALL were identi ed, including RBM15B, YTHDC1, YTHDC2, FTO, and HNRNPC among the 20 genes analyzed [11] .The ROC curve was used to evaluate the impact of m6A methylation related genes on the prognostic outcome of relapsed B-ALL.The ndings indicated that genes associated with m6A methylation played a role in the survival of relapsed B-ALL.The risk score of m 6 A methylation-related genes (YTHDC1 and FTO) might be a powerful biomarker for relapsed B-ALL survival. High expression levels of FTO predicted a poor prognosis, whereas YTHDC1 can be regarded as protective genes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations have firmly established the critical role of m 6 A modification in the etiology of AML and have identified singular molecular subtypes of AML based on changes in the m 6 A modifying enzymes (40,41). Despite these advances, most of these studies focused on the bulk tissues, while largely neglecting the relevance of the cell hierarchy to AML initiation and progression (42).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a well-established approach to develop tumor prognostic models based on m 6 A modification patterns for the evaluation and guidance of immunotherapy. By conducting comprehensive analyses of a substantial cohort of AML patients with a focus on m 6 A modifications [ 187 189 ], researchers systematically examined the overlaps and clustering within differentially expressed genes (DEGs). Based on these findings, they developed a scoring system known as the m 6 A score.…”
Section: Potential Of M 6 a In Cancer Therapymentioning
confidence: 99%